2021
DOI: 10.1038/s42003-020-01535-7
|View full text |Cite
|
Sign up to set email alerts
|

Fast automated detection of COVID-19 from medical images using convolutional neural networks

Abstract: Coronavirus disease 2019 (COVID-19) is a global pandemic posing significant health risks. The diagnostic test sensitivity of COVID-19 is limited due to irregularities in specimen handling. We propose a deep learning framework that identifies COVID-19 from medical images as an auxiliary testing method to improve diagnostic sensitivity. We use pseudo-coloring methods and a platform for annotating X-ray and computed tomography images to train the convolutional neural network, which achieves a performance similar … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…At the onset of the pandemic, classification of specific chest CT image anomalies has become key to support differential diagnosis of COVID-19-induced lung inflammation from pneumonia of other origin and the radiologist’s performance achieved sensitivity and specificity close to 90% [ 23 , 24 ]. Image classification by computerized deep learning methods, in particular convolutional neuronal networks, which rely on strong correlations between lesion areas in radiologic images and clinical indicators, achieve a specificity of >99% [ 25 ]. CT assessment includes the number, type, rate of anomaly development and particularly the distribution pattern in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…At the onset of the pandemic, classification of specific chest CT image anomalies has become key to support differential diagnosis of COVID-19-induced lung inflammation from pneumonia of other origin and the radiologist’s performance achieved sensitivity and specificity close to 90% [ 23 , 24 ]. Image classification by computerized deep learning methods, in particular convolutional neuronal networks, which rely on strong correlations between lesion areas in radiologic images and clinical indicators, achieve a specificity of >99% [ 25 ]. CT assessment includes the number, type, rate of anomaly development and particularly the distribution pattern in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the authors of [113] established a deep learning framework for detecting COVID-19 in X-ray and computed tomography images. ResBlock-A, ResBlock-B, and Control Gate Block made up a modular CNN-based classification system.…”
Section: Custom Deep Learning Techniquesmentioning
confidence: 99%
“…On the other hand, an accurate and quick diagnosis of COVID-19 can be achieved from CXR. In recent research [4][5][6], it is reported that CXRs examination has improved diagnosis, the readers are referred to [7][8][9][10][11][12][13][14]. However, manual analysis and interpretation of CXRs are not only quite time consuming, but it is also error-prone due to their subjectivity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an accurate and quick diagnosis of COVID-19 can be achieved from CXR. In recent research [ 4–6 ], it is reported that CXRs examination has improved the sensitivity of COVID-19 diagnostic. For additional computer aided applications of COVID-19 diagnosis, the readers are referred to [ 7–14 ].…”
Section: Introductionmentioning
confidence: 99%